Пошаговое объяснение:
Нехай початкова ширина прямокутника a₁ = х м,
тоді початкова довжина b₁= х+3 м,
S₁=x(x+3)=x²+3x
b₂= x+3-2=x+1
a₂= x+4
S₂=(x+1)(x+4)=x²+4x+x+4=x²+5x+4
x²+5x+4 -x²-3x=8
2x=8-4
x=4:2
x=2 м - початкова ширина
2+3=5 м - початкова довжина
Пошаговое объяснение:
Нехай початкова ширина прямокутника a₁ = х м,
тоді початкова довжина b₁= х+3 м,
S₁=x(x+3)=x²+3x
b₂= x+3-2=x+1
a₂= x+4
S₂=(x+1)(x+4)=x²+4x+x+4=x²+5x+4
x²+5x+4 -x²-3x=8
2x=8-4
x=4:2
x=2 м - початкова ширина
2+3=5 м - початкова довжина